PENGARUH PEMBERIAN PENGHARGAAN TERHADAP KINERJA ANGGOTA ORGANISASI KEMAHASISWAAN(STUDI KASUS PADA ORGANISASI AIESEC SURABAYA) - SURTI WAHYUNI, HERLIN (Jurnal Akuntansi AKUNESA, 2015)
This study aims to determine whether the Reward to the members of the organization AIESEC can improve the performance of members of the organization in an effort to achieve organizational goals. The reward is given measured using nominal dollars and member performance is measured using the Performance Appraisal (PA) of each individual who received the reward. These samples included 38 data during the period in 1415 that were selected using purposive sampling method. Data were analyzed using simple regression analysis. Based on test results concluded that the variable hasn’t give an effect on the performance of members of the organization. This means that performance of members is not affected by reward that given to them.Keyword: Reward, non-profit organization, Employee Performance